Scaling-Up the Use of Chili Fences for Reducing Human-Elephant Conflict Across Landscapes in Tanzania. (June 2016) - Chang'a, Alex; Souza de, Nick; Muya, John; Keyyu, Julius; Mwakatobe, Angela; Malugu, Lucas; Ndossi, Humphrey Peter; Konuche, Jonathan; Omondi, Raphael; Mpinge, Aloyce; Hahn, Nathan; Palminteri, Suzanne; et al.
Elephants ( Loxodonta africana ) raiding crops around Tanzanian national parks threaten farmers' lives and livelihoods, thus contributing to negative local attitudes towards wildlife. As a result, there is often tacit support for poaching among local communities, and elephants suffer through reprisal poisoning or wounding or through being shot as 'problem animals' by game wardens. Human-elephant conflict (HEC) is growing as the wildlands that still have elephants, especially around national parks, reserves, and wildlife corridors, are increasingly being settled. Sisal string fences soaked in engine oil mixed with ground chili ( Capsicum spp.) can dissuade elephants from entering fenced fields. For the last nine years, farmers around Mikumi National Park in Tanzania have been constructing these fences around ripening crops, and there have been no incidents of fences being broken by elephants. Community-based organizations (CBOs) that manage members' savings through village micro-credit associations help ensure the costs of materials and fence construction are met. Chili fences are rapidly becoming widespread, facilitated through farmer-to-farmer exchanges where teams of farmers demonstrate both the fences and the CBOs needed to support the project. We argue that promoting the use of chili fences, coupled with supporting CBOs, as a best practice within communities and government programs and budgets, will help reduce the need for HEC compensation, protect livelihoods, empower rural women, increase the food security of rural farmers, and help conserve elephants.